Strategies to Improve the Utilization of Tannin-Rich Feed Materials by Poultry - Medugu, C.I.; Saleh , B.; Igwebuike, J.U.; Ndirmbita, R.L. (International Journal of Poultry Science, 2012)
Tannins are well known as anti-nutritive factors that hinder the utilization of feeds by monogastric animals especially poultry. Tannins depressed growth rate and feed utilization by forming complexes with proteins and carbohydrates or inhibition of digestive enzymes. Unlike ruminant animals, poultry do not have microbes in their gastrointestinal tract to detoxify or reduce the effect of tannins, but several methods have been used to reduce the tannin content of poultry feeds for better utilization. These methods are mainly physical and chemical in nature. The physical methods are cooking, dehulling, autoclaving, toasting / roasting and soaking, while the chemical methods include, use of wood ash, addition of tallow, use of tannin binding agents, use of enzymes, germination and urea treatment. The choice of method(s) will depend on their effectiveness in reducing tannin and the cost involved.